Photosensitive composition, method for producing pattern, cured product, and electronic component
The photosensitive composition addresses the limitations of existing technologies by using a graft polymer and photoacid generator to create fine patterns with high sensitivity and low warpage stress, achieving excellent chemical resistance and resolution.
Patent Information
- Application Number
- CN202411597503.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-24
AI Technical Summary
Existing photosensitive compositions for semiconductor packaging fail to achieve high sensitivity, high resolution, low warpage stress, and excellent chemical resistance while maintaining low-temperature curing.
A photosensitive composition comprising a graft polymer, photoacid generator, thermal crosslinking agent, and basic compound, which allows for the formation of fine patterns with high sensitivity, resolution, and low warpage stress through UV exposure and alkaline development, with components like polyimide-poly(p-hydroxystyrene) and triarylsulfonium salt enhancing properties.
The composition achieves excellent sensitivity, high resolution, low warpage stress, and good chemical resistance after low-temperature curing, enabling effective pattern replication and improved mechanical properties.
Smart Images

Figure CN119179233A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photosensitive dielectric materials, and in particular to a photosensitive composition, a method for preparing a pattern, a cured product and an electronic component. Background Art
[0002] As semiconductor packaging density increases, PSPI materials are also gradually developing towards low-temperature curing, high sensitivity, high resolution, and low warpage stress.
[0003] There are literature reports on lowering the glass transition temperature of PI polymer and assisting with a thermal alkali generator (see WO2018225676A1). This method can achieve low-temperature curing at 200-230°C to obtain a negative PSPI cured product with excellent adhesion, but this method cannot achieve the requirements of high sensitivity, high resolution and low warpage stress.
[0004] Other literature reports the use of chemically imidized PI polymers with phenolic hydroxyl or carboxyl groups, assisted by a suitable crosslinking agent (see CN102575139A). This method can achieve low-temperature curing at 200-230°C, and obtain a positive PSPI cured product with excellent chemical resistance. However, this method has limited improvement in chemical resistance, and the sensitivity of this composition is generally low.
[0005] Other literature reports the use of polymers with phenolic hydroxyl groups, such as poly(p-hydroxystyrene) or phenolic resin, supplemented by a cross-linking agent and toughened with rubber particles (see WO2008026406A1), to obtain a composition that cures at 200°C, has a fast sensitivity, high resolution, and low warping stress. However, the cured product obtained in this way has poor mechanical properties and limited improvement in toughness, which may lead to reliability problems.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a photosensitive composition, a method for preparing a pattern, a cured product and an electronic component. The photosensitive composition provided by the embodiment of the present invention has excellent sensitivity, resolution and can form a fine pattern, and has low warpage stress after low-temperature curing, high chemical stability and adhesion.
[0008] The present invention is achieved in that:
[0009] In a first aspect, the present invention provides a photosensitive composition, which includes a component (a) a graft polymer selected from the compounds represented by the following formula 1:
[0010]
[0011] wherein Ar1 is selected from a tetravalent organic group, Ar2 is selected from a divalent organic group, R′ is selected from any one of an alkyl group, an alkoxy group, a cycloalkyl group and an aromatic group; m+n=5-200, n / (m+n)=0.05-1, k=2-10, x=0.5-10;
[0012] Component (b) a photoacid generator;
[0013] Component (c) thermal crosslinking agent: a crosslinking agent containing CH2OR", wherein R" is selected from hydrogen or a monovalent organic group;
[0014] Component (d) a basic compound.
[0015] In a second aspect, the present invention provides a method for preparing a pattern, comprising coating the photosensitive composition described in any one of the aforementioned embodiments on a supporting substrate;
[0016] Preferably, the method further comprises: drying, exposure, development and heating treatment in sequence after coating;
[0017] Preferably, the light source used in the exposure process is i-ray.
[0018] In a third aspect, the present invention provides a cured product, wherein the cured product is formed by curing the photosensitive composition according to any one of the aforementioned embodiments;
[0019] Preferably, the cured product includes a surface protection film or an interlayer insulating film.
[0020] In a fourth aspect, the present invention provides an electronic component comprising the cured product according to the above embodiment.
[0021] The present invention has the following beneficial effects: the portion of the photosensitive composition provided by the embodiment of the present invention that is exposed to ultraviolet light is easily soluble in an alkaline aqueous solution, while the portion that is not exposed to ultraviolet light is insoluble in an alkaline aqueous solution, thereby being able to effectively replicate fine patterns. The photosensitive composition has excellent sensitivity, high resolution, low warpage stress, high adhesion and good chemical resistance after low-temperature curing (180-200°C). BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1A schematic diagram of a semiconductor packaging structure provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0025] An embodiment of the present invention provides a photosensitive composition, which includes the following components:
[0026] Component (a) a graft polymer; component (b) a photoacid generator; component (c) a thermal crosslinking agent; and component (d) a basic compound.
[0027] The part of the photosensitive composition provided by the embodiment of the present invention that is exposed to ultraviolet light is easily soluble in an alkaline aqueous solution, while the part that is not exposed to ultraviolet light is insoluble in an alkaline aqueous solution, so that fine patterns can be effectively replicated. The photosensitive composition provided by the present invention increases the dissolution rate ratio (dissolution contrast) of the exposed part of the pattern to the unexposed part relative to the alkaline developer, so that the sensitivity and resolution are excellent. At the same time, the photosensitive composition has low warping stress after high temperature curing, and has excellent chemical resistance and adhesion.
[0028] Specifically, the main chain skeleton of the graft polymer of component (a) is preferably a polyimide polymer from the viewpoint of processability and heat resistance, and the graft chain skeleton is preferably a polyparahydroxystyrene polymer.
[0029] Furthermore, component (a) is more preferably a graft copolymer of polyimide-poly(p-hydroxystyrene), specifically a polymer having a structural unit represented by the following formula 1:
[0030]
[0031] wherein m+n is the number of repeating structural units of component (a), and m+n=5 to 200, for example, 5, 10, 15, 20, 25, 35, 40, 50, 70, 75, 80, 85, 95, 100, 110, 120, 135, 150, 160, 175, 180, 185, 190, 195 and 200, etc., any number between 5 and 200. When m+n is less than 5, the viscosity of the composition is too low, resulting in the composition being unable to be used as a thick film, and when m+n is greater than 200, the composition becomes too viscous, affecting coating. n / (m+n)=0.05~1, for example, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 and any value between 0.05-1.
[0032] The solubility of the composition in alkaline aqueous solution is derived from the phenolic hydroxyl group, so it is preferred to contain a structure of a certain proportion or more. More preferably, k=2 to 10. For example, 2, 4, 6, 8, 10 and any value between 2-10. Too large a k unit will cause the film toughness to begin to deteriorate. More preferably, x=0.5-10, for example, 0.5, 1, 3, 5, 7, 9, 10 and any value between 0.5-10. Too small an x unit will result in a large loss in the thickness of the developed film. Therefore, by adjusting the grafting amount of para-hydroxystyrene and the acetalization amount of the phenolic hydroxyl group, a photosensitive grafted composition with a moderate dissolution rate can be obtained.
[0033] Further, Ar1 is selected from a quaternary organic group, for example, Ar1 is selected from any one of the quaternary organic groups represented by the following formula 2, the same or different each time it appears:
[0034]
[0035] Wherein, R1-R8 are all monovalent organic groups, and X is a divalent group.
[0036] Specifically, R1-R8 are each independently selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl; preferably, R1-R8 are each independently selected from any one of hydrogen, fluorine atom, methyl and trifluoromethyl.
[0037] X is selected from any one of an oxygen atom, a C1-C5 substituted or unsubstituted alkylene group, a sulfur atom, a sulfone group and a carbonyl group, and X is selected from any one of an oxygen atom, a methylene group, a sulfur atom, a sulfone group, a carbonyl group, C(CH3)2 and C(CF3)2.
[0038] Specifically, in Formula 1, Ar1 is a tetravalent organic group, generally a residue of tetracarboxylic dianhydride or its derivatives with an amide ester structure formed by tetracarboxylic dianhydride or its derivatives and diamine, preferably a tetravalent aromatic group, preferably a residue of tetracarboxylic dianhydride or its derivatives having the following structure, wherein all four binding sites are present on the aromatic ring. Examples of such tetracarboxylic dianhydrides include: pyromellitic dianhydride, 3,3',4,4'biphenyltetracarboxylic dianhydride, 2,3,3',4'biphenyltetracarboxylic dianhydride, 2,2',3,3'biphenyltetracarboxylic dianhydride, 3,3',4,4'benzophenonetetracarboxylic dianhydride, 2,2',3,3'benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, and 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride. 、1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride、1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride、bis(3,4-dicarboxyphenyl)methane dianhydride、bis(2,3-dicarboxyphenyl)methane dianhydride、bis(3,4-dicarboxyphenyl)sulfone dianhydride、bis(3,4-dicarboxyphenyl)ether dianhydride、1,2,5,6-naphthalenetetracarboxylic dianhydride、9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride、 Aromatic tetracarboxylic dianhydrides such as 9,9-bis{4(3,4-dicarboxyphenoxy)phenyl}fluorene dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 2,3,5,6-pyridinetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, and 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, and aliphatic tetracarboxylic dianhydrides such as butanetetracarboxylic dianhydride and 1,2,3,4-cyclopentanetetracarboxylic dianhydride, etc. These may be used alone or in combination of two or more.
[0039] Further, Ar2 is selected from a divalent organic group, for example, Ar2 is selected from any one of the divalent organic groups shown in Formula 3, the same or different each time it appears:
[0040]
[0041] Among them, R9-R 20 are all monovalent organic groups, and Y is a divalent group.
[0042] Specifically, R9-R 20 Each is independently selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl; preferably, R9-R 20 Each is independently selected from any one of hydrogen, a fluorine atom, a methyl group and a trifluoromethyl group.
[0043] Y is selected from any one of an oxygen atom, a C1-C5 substituted or unsubstituted alkylene group, a sulfur atom, a sulfone group and a carbonyl group; Y is selected from any one of an oxygen atom, a methylene group, a sulfur atom, a sulfone group, a carbonyl group, C(CH3)2 and C(CF3)2.
[0044] Furthermore, in Formula 1, Ar2 is a divalent organic group, generally an amide structure formed by an amino acid and a diamine, and is derived from an amino acid residue, preferably a divalent aromatic group, preferably an amino acid residue having the following structure, wherein both binding sites are present on the aromatic ring, and such amino acids include p-aminobenzoic acid, m-aminobenzoic acid, ortho-aminobenzoic acid, etc. They can be used alone or in combination of two or more.
[0045] In addition, in order to improve adhesion to the substrate, as long as the heat resistance is not damaged, the Ar2 part can be selected to copolymerize with a certain proportion of aliphatic groups with a siloxane structure, preferably 1-10 mol% of bis(3-aminopropyl)tetramethyldisiloxane, bis(p-aminophenyl)octamethylpentasiloxane, etc.
[0046] The terminal groups of the aromatic polyamide shown in Formula 1 are carboxylic acid or amine depending on the input ratio of Ar1 and Ar2. As required, one or two end-capping agents may react with the polymer ends to make one or both ends saturated aliphatic groups, unsaturated aliphatic groups, carboxyl groups, phenolic hydroxyl groups, sulfonic acid groups or mercapto groups, etc. In this case, the end-capping rate is preferably 30-100%.
[0047] It should be noted that: (1) the above R1-R 20 The halogen mentioned in is not limited to F, and may also be bromine, chlorine, and the like.
[0048] (2) The above R1-R 20 The C1-C5 substituted or unsubstituted alkyl mentioned in the above may be a C1-C3 substituted or unsubstituted alkyl, for example, it may be an unsubstituted alkyl such as methyl, ethyl, propyl, n-butyl, isopropyl, isobutyl, tert-butyl, or a substituted alkyl such as trifluoromethyl, trifluoroethyl, difluoromethyl, trichloromethyl.
[0049] (3) The above R1-R 20 The C1-C5 substituted or unsubstituted alkylene mentioned in the above may be C1-C3 unsubstituted alkylene, such as methylene, ethylene, propylene and other unsubstituted alkylene, or may be C1-C3 substituted alkylene, such as halogen (fluorine, bromine, chlorine) substituted methylene, halogen substituted ethylene, etc.
[0050] R′ is selected from any one of an alkyl group, an alkoxy group, a cycloalkyl group and an aromatic group, including but not limited to ethyl, propyl, butyl, cyclohexyl and phenyl.
[0051] The molecular weight of component (a) is preferably 3000 to 200000, more preferably 5000 to 100000, as a weight average molecular weight. The molecular weight here is a value measured by gel permeation chromatography and converted from a standard polystyrene calibration curve.
[0052] In the embodiments of the present invention, the graft polymer having the structural unit shown in Formula 1 is generally prepared by polycondensation of dianhydride and diamine to obtain a polyamic acid polymer, which is then chemically imidized to obtain a polyimide polymer, which is then chloromethylated and xanthated to obtain a macromolecular initiator, and then grafted polymerized to obtain a graft copolymer of polyimide-g-poly(p-hydroxystyrene), and finally the graft copolymer is acetalized using a vinyl ether compound to obtain the graft copolymer of the present invention.
[0053] Specifically, in the first step, polyamic acid can be prepared by reacting diamine with dianhydride, and then polyimide can be prepared by chemical imidization. In the second step, the polyimide is chloromethylated and xanthate-esterified to obtain a macroinitiator. In the third step, the macroinitiator prepared in the second step is grafted with p-hydroxystyrene by RAFT polymerization to prepare a graft polymer. In the fourth step, the graft copolymer is acetalized with a vinyl ether compound to obtain the graft copolymer of the present invention. The conditions and operations of the above steps are well known to those skilled in the art and will not be described in detail in the embodiments of the present invention.
[0054] The photoacid generator of component (b) is a compound that generates acid when irradiated with active light or radiation. For example, any one or a combination of two or more of diaryliodonium salts, triarylsulfonium salts, imide sulfonate derivatives and oxime sulfonate compounds. In terms of thermal stability and sensitivity, component (b) is preferably a triarylsulfonium salt, and more preferably used in combination with a sensitizer.
[0055] The sulfonate anion contained in the triarylsulfonium salt contained in the photosensitive composition of the embodiment of the present invention may include an arylsulfonate anion substituted with a fluorine atom or an organic group having a fluorine atom, an alkanesulfonate anion, and the like.
[0056] Specifically, the triarylsulfonium salt is selected from any one or a combination of two or more of the following specific examples, but the triarylsulfonium salt provided by the embodiment of the present invention is not limited to the following specific examples or their combinations.
[0057]
[0058] Further, examples of diaryliodonium salts include diphenyliodonium trifluoroacetate, diphenyliodonium trifluoromethanesulfonate, 4-methoxyphenylphenyliodonium trifluoromethanesulfonate, 4-methoxyphenyliodonium trifluoroacetate, phenyl, 4-(2'-hydroxy-.1'-tetradecyloxy)phenyliodonium trifluoromethanesulfonate, and the like;
[0059] Imidosulfonate derivatives include, but are not limited to, trifluoromethylsulfonyloxybicyclo[2.2.1]heptane-5-terminal dicarboximide, succinimide trifluoromethylsulfonate, phthalimide p-toluenesulfonate, phthalimide trifluoromethylsulfonate, N-hydroxynaphthalimide methanesulfonate, examples of which include N-hydroxy-5-norbornene-2,3-dicarboximide propanesulfonate.
[0060] Among compounds that generate an acid upon irradiation with active light or radiation, oxime compounds are preferred, and oxime sulfonate compounds are more preferred from the viewpoints of sensitivity, resolution, dielectric constant, dimensional stability, etc. As oxime sulfonate compounds, i.e. compounds having an oxime sulfonate residue, compounds having an oxime sulfonate residue represented by the following formula can be preferably exemplified.
[0061]
[0062]
[0063] In the photosensitive resin composition provided by an embodiment of the present invention, based on 100 parts by weight of the component (a), the content of the component (b) is 1-5 parts by weight, for example, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, or any value between 1-5 parts by weight.
[0064] The photoacid generator provided in the embodiment of the present invention can be used alone or in combination of two or more. When two or more are used in combination, it is preferred to combine to generate two or more organic acid compounds with different total atomic numbers excluding hydrogen atoms.
[0065] The photosensitive composition provided by the embodiment of the present invention, for the purpose of easily obtaining a cured film, further contains (c) a thermal crosslinking agent, which is a crosslinking agent having a -CH2OR" (R" is a hydrogen atom or a monovalent organic group) group, and in the heat treatment process after coating, exposing and developing the photosensitive polymer composition of the present invention, the crosslinking agent reacts with the polymer as component (a) to crosslink, or a compound that polymerizes itself during the heat treatment process. In addition, the crosslinking agent has an affinity for alkaline aqueous solutions and can increase the dissolution rate in alkaline aqueous solutions.
[0066] In an embodiment of the present invention, component (c) is a cross-linking agent having a -CH2OR" (R" is a hydrogen atom or a monovalent organic group) group in its structure. The compound can have at least one of the group, but preferably has at least two. Component (c) is selected from the compounds represented by the following formula 4-2-1 or 4-2-2.
[0067]
[0068] In formula 4-2-1, R21 are each independently a hydrogen atom or a monovalent organic group, R 22 Each of them is independently a hydrogen atom or a monovalent organic group, and may be combined with each other to form a ring structure which may have a substituent.
[0069] The following formula 4-2-1-1 shows specific examples of the compound represented by formula 4-2-1. These compounds can be used alone or in combination of two or more.
[0070]
[0071] Among them, R 25 is an alkyl group having 1 to 20 carbon atoms, preferably an alkyl group having 1 to 6 carbon atoms, R 26 It is an alkyl group having 1 to 10 carbon atoms.
[0072] The following formula 4-2-2-1 shows specific examples of the compound represented by formula 4-2-2. These compounds can be used alone or in combination of two or more.
[0073]
[0074] In formula 4-2-2, R 23 is selected from a hydrogen atom or a monovalent organic group, R 23 Preferably, it is hydrogen, alkyl or alkenyl. The number of carbon atoms in the alkyl or alkenyl group is preferably 1 to 20. 24 is selected from a monovalent organic group, R 24 It is preferably an alkyl group, an alkenyl group, an alkoxyalkyl group or a hydroxymethyl group, and the number of carbon atoms is preferably 1-20. n is an integer of 1-4, and X is selected from a single bond or an organic group with valence of 1-4. Examples include alkyl groups with carbon atoms of 1-10, alkylene groups with carbon atoms of 2-10 (such as ethylene, etc.), arylene groups with carbon atoms of 6-30 (such as phenylene, etc.), or groups obtained by replacing part or all of the hydrogen atoms of these hydroxy groups with halogen atoms such as fluorine atoms. These groups may further include phenyl, sulfone, carbonyl, ether bond, thioether bond, amide bond, etc. a is an integer of 1-4, and b is an integer of 0-3. When a is 2, 3 or 4, R 23 Same or different, when b is 2 or 3, R 24 Same or different.
[0075] The purity of the compound represented by the above formula 4-2 is preferably 75% or more, more preferably 85% or more. When the purity is 85% or more, the storage stability is excellent, and the crosslinking reaction of the polyimide composition can be fully carried out. In addition, since the unreacted groups that become water-absorbing groups can be reduced, the water absorption of the polyimide composition can be reduced. As a method for obtaining a high-purity thermal crosslinking agent, recrystallization, distillation, etc. can be cited. The purity of the thermal crosslinking agent can be obtained by liquid chromatography.
[0076] Relative to 100 parts by mass of the polyimide of component (a), the content of the thermal crosslinking agent of component (c) is preferably 5 parts by mass or more, more preferably 10 parts by mass or more. If it is 5 parts by mass or more, the crosslinking density of the cured film is improved, the chemical resistance is high, and there is low curing warpage, and if it is 10 parts by mass or more, the chemical resistance is higher, the low curing warpage is better, and higher mechanical properties can be obtained at the same time. In addition, from the perspective of composition storage stability and mechanical strength, it is preferably less than 30 parts by mass.
[0077] Furthermore, the content of c is 5-30 parts, for example, 5 parts, 7 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, etc., any value between 5-30 parts.
[0078] The photosensitive composition of the embodiment of the present invention further comprises a component (d) containing a basic compound to reduce the change in performance over time from exposure to heating. As the basic compound, a compound having a structure shown in Formula 5 below can be preferably cited.
[0079]
[0080] Wherein, A, Y, and Q may be one of alkyl, alkoxy, and cyclic alkyl, respectively. For example, they include but are not limited to ethyl, ethoxy, ethylethoxy, and cyclohexyl. The following formula 5-1 represents a specific example of the compound represented by formula 5, and the components may be used alone or in combination of two or more of these compounds.
[0081]
[0082] In the photosensitive composition provided by an embodiment of the present invention, based on 100 parts by weight of the component (a), the content of the component (d) is 0.001-2 parts by weight, for example, 0.001 parts by weight, 0.01 parts by weight, 0.1 parts by weight, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, or any other value between 0.001 and 2 parts by weight.
[0083] In the embodiment of the present invention, the ratio of the photoacid generator to the basic compound is preferably acid generator / basic compound (molar ratio) = 2.5 to 300. That is, from the viewpoint of sensitivity and resolution, the molar ratio is preferably 2.5 or more, and from the viewpoint of suppressing the reduction in resolution caused by the thickening of the relief pattern after exposure to heat treatment over time, it is preferably 300 or less. The acid generator / basic compound (molar ratio) is more preferably 5.0 to 200, and further preferably 7.0 to 150.
[0084] The photosensitive composition provided in the embodiment of the present invention further contains (e) a silane coupling agent, which is generally an organic silane compound. Examples of the organic silane compound include: γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, vinyl triethoxysilane, vinyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-acryloxypropyl trimethoxysilane, γ-ureidopropyl triethoxysilane, Silane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, triethoxysilylpropylethyl carbamate, 3-(triethoxysilyl)propylsuccinic anhydride, phenyltriethoxysilane, phenyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(l,3-dimethylbutylene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc.
[0085] When an organosilane compound is included, the adhesion between the photosensitive polyimide composition and the substrate after curing can be improved. When an organosilane compound is included, the content of the organosilane compound is more preferably 0.5-15 parts by mass, and more preferably 0.5-10 parts by mass relative to 100 parts by mass of component (a). For example, any value between 0.5-15 parts such as 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 1 part, 11 parts, 12 parts, 13 parts, 14 parts and 15 parts.
[0086] The polyimide composition of the present invention further contains (f) a solvent, preferably an organic solvent. For example, ketones, esters, lactones, ethers, halogenated hydrocarbons, hydrocarbons, etc. can be used. Specific examples include polar solvents such as γ-butyrolactone, N-methyl-2-pyrrolidone, N-acetyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethyl sulfoxide, hexamethylphosphoric triamide, dimethylimidazolidinone, tetraethyl urea, tetramethyl urea, ethyl lactate, 3-methoxy-N,N-dimethylpropaneamide and N-acetyl-ε-caprolactam. Other examples of the invention include acetone, diethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methyl acetate, ethyl acetate, butyl acetate, diethyl oxalate, diethyl malonate, diethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, dichloromethane, 1,2-dichloroethane, 1,4-dichlorobutane, trichloroethane, chlorobenzene, o-dichlorobenzene, hexane, heptane, octane, benzene, toluene, xylene, 1-methoxy-2-propanol, 1-methoxy-2-acetoxypropane, and propylene glycol 1-monomethyl ether 2-acetate. Component (f) may be used alone or in combination of two or more.
[0087] When component (f) is included, the amount of component (e) is preferably 50-1000 parts by mass, more preferably 100-200 parts by mass, relative to 100 parts by mass of component (a), for example, 50 parts, 60 parts, 70 parts, 100 parts, 150 parts, 200 parts, 300 parts, 400 parts, 500 parts, 600 parts, 700 parts, 800 parts, 900 parts and 1000 parts, and any value between 50 and 1000 parts.
[0088] The present invention may further contain (g) a leveling agent, and the leveling agent may be a surfactant, so as to improve the coating property between the substrate and the substrate. Examples of the surfactant include fluorine-based surfactants such as Fluorad (trade name, manufactured by Sumitomo 3M Co., Ltd.), Megafac (trade name, manufactured by DIC Co., Ltd.), and Surflon (trade name, manufactured by Asahi Glass Co., Ltd.); organic siloxane surfactants such as KP341 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.), DBE (trade name, manufactured by Chisso Corporation), Polyflow, Glanol (trade name, manufactured by Kyoeisha Chemical Co., Ltd.), and BYK (trade name, manufactured by BYK-Chemie GmbH); acrylic polymer surfactants such as Polyflow (trade name, manufactured by Kyoeisha Chemical Co., Ltd.); and the like.
[0089] When component (f) is included, the content of component (g) is 100-1000 ppm relative to 100 parts by mass of component (a), for example, it is any value between 100-1000 ppm such as 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm and 1000 ppm.
[0090] Further, the preparation method of the photosensitive composition provided by the embodiment of the present invention is described. For example, by uniformly mixing the above-mentioned (a)-(d) components and the (e)-(g) components used as needed, a photosensitive composition can be obtained. As a dissolving method, stirring and heating can be cited. When heating, it is preferred to set the heating temperature within a range that does not destroy the performance of the polyimide composition, usually room temperature-80°C. In addition, the dissolution order of each component is not particularly limited, for example, including a method of dissolving in sequence starting from compounds with low solubility. In addition, for components such as surfactants and a portion of adhesion improvers that are prone to generate bubbles when stirred and dissolved, poor dissolution of other components caused by the generation of bubbles can be prevented by adding them last after dissolving other components.
[0091] The obtained photosensitive polyimide composition is preferably filtered using a filter to remove impurities and particles. The filter pore size is 0.5-0.02 μm, for example, 0.5 μm, 0.2 μm, 0.1 μm, 0.05 μm, 0.02 μm, etc., but not limited to this. The material of the filter includes polypropylene (PP), polyethylene (PE), nylon (NY), polytetrafluoroethylene (PTFE), etc., preferably polyethylene and nylon. When the photosensitive polyimide composition contains inorganic particles, it is preferred to use a filter with a pore size larger than the particle size of these inorganic particles.
[0092] Furthermore, a cured product provided in an embodiment of the present invention can be obtained by curing the above-mentioned photosensitive composition. The cured product of the present invention can be used as a patterned cured film or a non-patterned cured film.
[0093] The method for manufacturing a patterned cured film or the method for preparing a pattern comprises, for example, a step of coating the above-mentioned photosensitive composition on a substrate and drying it to form a photosensitive polyimide film (film forming step); a step of exposing the photosensitive polyimide film (exposure step); a step of diffusing the photosensitive composition with acid (post-exposure baking step); a step of developing the exposed photosensitive polyimide film with an alkaline aqueous solution to form a patterned polyimide film (development step); and a step of heating the patterned polyimide film (heating step). The method for manufacturing a non-patterned cured film comprises, for example, the above-mentioned film forming step and heating step. It may also further comprise an exposure step.
[0094] In the film forming process, the photosensitive composition is applied on a metal substrate such as Cu, a glass substrate, a semiconductor, a metal oxide insulator (such as TiO2, SiO2, etc.), a supporting substrate such as silicon nitride, etc., for example, by dipping, spraying, screen printing, spin coating, etc. From the viewpoint of operability, the applied positive photosensitive polyimide composition can also be used by drying by heating (for example, 90-150° C., 1-5 minutes) using a hot plate, an oven, etc. The supporting substrate can also be cleaned with acetic acid, etc. before coating. The film thickness of the obtained photosensitive polyimide film is preferably 5-20 μm.
[0095] In the exposure step, for example, the photosensitive polyimide film formed on the substrate is irradiated with the above-mentioned active light rays through a mask. From the viewpoint of transparency of the component (a), irradiation with i-rays can be preferably used.
[0096] In the developing process, for example, the exposure portion of the photosensitive polyimide film after the exposure process is removed with a developer, so that the photosensitive polyimide film is patterned. As a developer, in the case of an alkali-soluble photosensitive composition, an alkali aqueous solution such as sodium hydroxide, potassium hydroxide, sodium silicate, ammonia, ethylamine, diethylamine, triethylamine, triethanolamine, tetramethylammonium hydroxide (TMAH) can be suitably used. The alkali concentration of these aqueous solutions is preferably set to 0.1-10 mass %. Furthermore, alcohols or surfactants can also be added to the above-mentioned developer and used. They can be respectively matched in a range of preferably 0.01-10 mass parts, more preferably 0.1-5 mass parts relative to 100 mass parts of the developer. The photosensitive polyimide film after patterning is referred to as a patterned polyimide film.
[0097] In the heating process, the photosensitive composition can be cured by heating the pattern polyimide film or the photosensitive polyimide film. In particular, the film obtained by curing the pattern polyimide film is called a pattern cured film. The heating temperature is preferably 150-250°C, preferably less than or equal to 230°C, more preferably greater than or equal to 170°C, and further preferably 180-200°C. The heating time is preferably 20 minutes to 6 hours, more preferably 30 minutes to 3 hours. Multi-stage heating can also be performed. The heat treatment can be performed using, for example, a quartz tube furnace, a hot plate, a rapid thermal annealing furnace, a vertical diffusion furnace, an infrared curing furnace, an electron beam curing furnace, and a microwave curing furnace. In addition, any one of the inert atmospheres such as the atmosphere or nitrogen can be selected, but when carried out under nitrogen, oxidation of the pattern can be prevented, so an inert atmosphere such as nitrogen is preferred.
[0098] The cured product of the present invention can be used as an interlayer insulating film, a surface protective film, or the like.
[0099] The interlayer insulating film and the surface protection film of the present invention can be used for electronic components, etc. The electronic components of the present invention can be used for semiconductor devices, etc. The semiconductor devices can be used for various electronic devices, etc. The semiconductor packaging structure schematic diagram of the present invention is as follows Figure 1 shown.
[0100] This exhibits excellent rust prevention and adhesion effects on a supporting substrate (particularly a copper substrate or a copper alloy substrate), and can suppress discoloration of the cured film or the supporting substrate (particularly a copper substrate or a copper alloy substrate).
[0101] As the semiconductor device, for example, semiconductor packages such as wafer level chip size package (WLCSP) and fan-out wafer level package (FOWLP) can be cited. In addition, the interlayer insulating film and surface protection film of the present invention can also be used for a circuit forming substrate, and the circuit forming substrate can be used for a hard disk drive suspension, a flexible wiring board, etc.
[0102] The substances corresponding to the abbreviations of the compounds provided in the embodiments of the present invention are as follows:
[0103] ODA: 4,4-diaminodiphenyl ether; SiDA: 1,3-bis(3-aminopropyl)tetramethyldisiloxane; ODPA: 4,4'-oxydiphthalic anhydride; Py: pyridine; Et2A: acetic anhydride; PhA: phthalic anhydride; NMP: N-methyl 2-pyrrolidone; TMAH: tetramethylammonium hydroxide; CMM: chloromethyl methyl ether; SnCl4: tin tetrachloride; AIBN: azobisisobutyronitrile; 4-HS: p-hydroxystyrene; EVE: ethyl vinyl ether; PTST: p-toluenesulfonic acid pyridinium salt; St: styrene; 6FAP: 3,3-diamino-4,4-dihydroxydiphenyl-hexafluoropropane.
[0104] The component (a) synthesized in the following synthesis example of the present invention was tested for molecular weight, grafting amount and grafting rate. The specific testing method is as follows:
[0105] (1) Determination of molecular weight
[0106] The number average molecular weight was determined by gel permeation chromatography (GPC) under the following conditions in terms of standard polystyrene: The measurement was performed using 1 mL of a solution containing 0.5 mg of A and a solvent of [tetrahydrofuran (THF) / dimethylformamide (DMF) = 1 / 1 (volume ratio)].
[0107] Measuring device: Detector: L4000UV manufactured by Hitachi, Ltd.; Pump: L6000 manufactured by Hitachi, Ltd.
[0108] C-R4A Chromatopac manufactured by Shimadzu Corporation.
[0109] Determination conditions: chromatographic column Gelpack GL-S300MDT-5×2; eluent: THF / DMF=1 / 1 (volume ratio), LiBr (0.03 mol / L), H3PO4 (0.06 mol / L); flow rate: 1.0 mL / min, detector: UV270 nm.
[0110] (2) Determination of grafting ratio n / (m+n)
[0111] Measurement equipment: AV400M manufactured by Bruker BioSpin.
[0112] Magnetic field strength: 400 MHz; Reference substance: tetramethylsilane (TMS); Solvent: dimethyl sulfoxide (DMSO).
[0113] (3) Determination of grafting amount k
[0114] Measurement equipment: AV400M manufactured by Bruker BioSpin
[0115] Magnetic field strength: 400 MHz; Reference substance: tetramethylsilane (TMS); Solvent: dimethyl sulfoxide (DMSO).
[0116] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0117] Synthesis example 1
[0118] The embodiment of the present invention provides a method for preparing a graft polymer A1, comprising:
[0119] Under a dry nitrogen stream, 20.02 g (0.1 mol) of ODA was dissolved in 200 g of NMP, and the resulting solution was cooled to -10°C. Subsequently, 26.37 g (0.085 mol) of ODPA was slowly added thereto so that the temperature of the reaction solution did not exceed 0°C, and stirring was continued for 3 hours, and then 4.44 g (0.03 mol) of PhA was added, and stirring was continued for 2 hours at room temperature to obtain a polyamic acid solution.
[0120] 39.55g Py and 30.6g Et2A were added to the polyamic acid solution, the temperature was raised to 120°C, and the reaction was continued for 12h. After the reaction was completed, the solution was poured into 2L deionized water for precipitation, washed with water, and vacuum dried at 80°C to obtain a polyimide resin, the structural formula of which is shown below:
[0121]
[0122] Dissolve 5g of dried polyimide resin in 30mL of dichloroethane, add 80μL SnCll4, heat to 70℃, slowly drop 3mL of CMM into the system, and stir for 5h. After the reaction is completed, pour the solution into 300mL of methanol for precipitation, wash, and dry at 80℃ for 12h to obtain chloromethylated polyimide resin, the structural formula of which is shown below:
[0123]
[0124] Dissolve 1g of dried chloromethylated polyimide resin in 20mL NMP. After dissolution, add 0.1g potassium ethyl xanthate and react at room temperature for 24h. After the reaction is completed, pour the solution into 200mL deionized water for precipitation and dry at 80℃ for 12h to obtain a macromolecular initiator, the structural formula of which is shown below:
[0125]
[0126] Dissolve 1g of the dried macromolecular initiator in 20mL of NMP, heat to 65°C after dissolution, drop 3g of 4-HS, and then add 0.01g of AIBN to carry out RAFT polymerization, and continue the reaction for 2h. After the reaction is completed, cool the solution to room temperature, pour it into 200mL of deionized water for precipitation, wash it with ethanol several times, and dry it at 80°C for 12h to obtain polyimide-g-poly(p-hydroxystyrene) graft copolymer A1, the structural formula of which is shown below, the molecular weight is 39000, n / (m+n)=40%, k=3.5.
[0127]
[0128] Synthesis example 2
[0129] The embodiment of the present invention provides a method for preparing a graft polymer A2, comprising:
[0130] Dissolve 1g of dried polyimide-g-poly(p-hydroxystyrene) in 20mL NMP, heat to 35°C after dissolution, add 2g EVE and 0.1g PTST, and continue to react for 5h. After the reaction, cool the solution to room temperature, pour into 200mL deionized water for precipitation, wash with ethanol several times, and dry at 80°C for 12h to obtain graft copolymer A2, the structural formula of which is as follows: molecular weight 39050, n / (m+n)=40%, k=3.5, x=2.5.
[0131]
[0132] Synthesis example 3
[0133] The embodiment of the present invention provides a method for preparing a graft polymer A3, comprising:
[0134] Add 192g methanol, 172.32g 4-HS, 19.53g St and 15g AIBN to a four-necked flask in turn, stir and dissolve until clear. Vacuum and replace the air in the reaction vessel with nitrogen, heat to 75°C, react for 18h, and stop the reaction. Slowly add the prepared sodium methoxide (0.4g) solution to the reaction system, react for 6h, extract 2 to 3 times with n-heptane and reaction liquid in a mass ratio of 1:1, remove the unreacted monomers and initiators in the reaction liquid, replace the methanol in the reaction liquid with PGMEA, and obtain the required concentration of PGMEA solution. PHS resin A3 is obtained, and its structural formula is shown below. The ratio of p-hydroxystyrene to styrene repeating units is 80 / 20, that is, m is 20 and n is 80.
[0135]
[0136] Synthesis example 4
[0137] The embodiment of the present invention provides a method for preparing a graft polymer A4, comprising:
[0138] Under a dry nitrogen flow, 36.63 g (0.1 mol) of 6FAP was dissolved in 200 g of NMP, and the resulting solution was cooled to -10°C. Subsequently, 26.37 g (0.085 mol) of ODPA was slowly added thereto so that the temperature of the reaction solution did not exceed 0°C, and stirring was continued for 3 hours, and then 4.44 g (0.03 mol) of PhA was added, and stirring was continued for 2 hours at room temperature to obtain a polyamic acid solution.
[0139] 39.55 g of Py and 30.6 g of Et2A were added to the polyamic acid solution, the temperature was raised to 120°C, and the reaction was continued for 12 hours. After the reaction was completed, the solution was poured into 2 L of deionized water for precipitation, washed with water, and vacuum dried at 80°C to obtain polyimide resin A4, the structural formula of which is shown below.
[0140]
[0141] Examples 1-15 and Comparative Examples 1-3
[0142] The photosensitive compositions of Examples 1-15 and Comparative Examples 1-3 were prepared according to the components and proportions shown in Table 1-3. The amounts of each component in Table 1-3 are parts by mass of each component relative to 100 parts by mass of component (a).
[0143] Among them, the selection of components (b) to (f) used in Tables 1 to 3 is as follows:
[0144] Component (b): Photoacid generator
[0145]
[0146] Component (c): thermal crosslinking agent
[0147]
[0148] Component (d): basic compound
[0149] DIA:2,6-Diisopropylaniline
[0150] PEA:N-phenyldiethanolamine
[0151] Component (e): γ-ureapropyltriethoxysilane
[0152] Component (f): solvent
[0153] f1: GBL (γ-butyrolactone)
[0154] f2: EL (ethyl lactate)
[0155] Table 1 Photosensitive composition ingredients
[0156]
[0157]
[0158] Table 2 Photosensitive composition ingredients
[0159]
[0160] Table 3 Photosensitive composition ingredients
[0161]
[0162] The performance of the photosensitive compositions prepared in Examples 1-15 and Comparative Examples 1-3 was evaluated as follows:
[0163] (1) Preparation of developing film
[0164] The photosensitive compositions (varnishes) prepared in Examples 1-15 and Comparative Examples 1-3 were spin-coated on an 8-inch silicon wafer and then heat-treated (prebaked) at 120°C for 3 minutes using a hot plate (coating and developing device Mark-7 manufactured by Tokyo Electron Ltd.) to prepare a prebaked film with a thickness of 6 μm. An i-line stepper (manufactured by Nikon Corporation, NSR-2005i9C) was used at 50 to 400 mJ / cm 2 Exposure, 10mJ / cm 2 The obtained prebaked film was exposed in steps of . After exposure, the photosensitive polyimide composition was exposed at 100° C. for 1 minute and then baked. After the photosensitive polyimide composition was baked after exposure, it was developed for 90 seconds using a 2.38 wt % tetramethylammonium (TMAH) aqueous solution (manufactured by Mitsubishi Gas Chemical Co., Ltd., ELM-D), and then rinsed with pure water to obtain a developed film.
[0165] (2) Evaluation of film thickness loss
[0166] The film thickness after prebaking and development was measured using a film thickness measuring device Filmtris F50 at a refractive index of 1.63. A film thickness loss of less than 0.2 μm was considered A, a film thickness loss of 0.2-1 μm was considered B, a film thickness loss of 1-2 μm was considered C, and a film thickness loss of more than 2 μm was considered D. The results are shown in Table 4.
[0167] (3) Determination of warpage
[0168] The varnish was applied by spin coating using a coating and developing device ACT-8 and prebaked so that the film thickness after prebaking at 120°C for 3 minutes was 10 μm. Then, an inert oven was used to raise the temperature to 200°C at a rate of 3.5°C / min under the condition of an oxygen concentration of less than 20 ppm, and heat treated at 200°C for 1 hour. The wafer was taken out when the temperature became less than 50°C, and the cured film was measured using a pressure device FLX2908 (manufactured by KLA Tencor). As a result, the situation above 35 MPa was considered insufficient (D), the situation above 30 MPa and less than 35 MPa was considered good (C), the situation above 20 MPa and less than 30 MPa was considered better (B), and the situation less than 20 MPa was considered the best (A). The results are shown in Table 4.
[0169] (4) Sensitivity evaluation
[0170] After exposure and development, the exposure amount (called the optimal exposure amount Eop) that forms a 20μm line and space pattern (1L / 1S) with a width of 1:1 is used as the sensitivity. If Eth is 200mJ / cm 2 Below 150 mJ / cm2, it can be judged as high sensitivity. More preferably, it is 150 mJ / cm2. 2 The results are shown in Table 4 below.
[0171] (5) Chemical resistance evaluation
[0172] Apply to the above solidified product with a pipette. Place the solidified product after application in a nitrogen oven at 200°C and keep it for 60 minutes. Then, transfer the solidified product from the hot plate and cool it to room temperature. Wash the cooled solidified product with NMP at 45°C and soak it for 1 hour, then measure the film thickness.
[0173] The film thickness change rate (%) was calculated from the film thickness change. A positive value means that the film expanded, and a negative value means that the film dissolved. The results are shown in Table 4.
[0174] (6) Adhesion evaluation
[0175] A cured product was produced on a Cu substrate using the above-mentioned method for producing a cured product. The cured product was cut into 10×10 grids using a crosscut guide (manufactured by COAT-TECH Co., Ltd.) with a shear knife, thereby dividing the cured product into 100 small pieces.
[0176] An adhesive tape (manufactured by 3M Japan Ltd.) was attached to the cured product, and then the adhesive tape was peeled off. The adhesiveness was evaluated as follows based on the number of small pieces of the cured product peeled off from the substrate when the adhesive tape was peeled off.
[0177] A: The number of remaining grids is 100 to 80.
[0178] B: The number of remaining grids is less than 80.
[0179] The results are shown in Table 4.
[0180] (7) Evaluation of elongation at break
[0181] The varnish was applied by spin coating using a coating and developing device ACT-8 and prebaked to a film thickness of 10 μm after prebaking at 120°C for 3 minutes. Then, the temperature was raised to 200°C at a rate of 3.5°C / min under an oxygen concentration of 20 ppm or less using an inert oven, and heat treated at 200°C for 1 hour. When the temperature became below 50°C, the wafer was taken out, the film was peeled off, and cut into 4 mm × 8 mm strips, and tensile testing was performed using DAGE4000.
[0182] The results showed that the elongation at break was 30% or more as excellent (A), 20-30% as good (B), 10-20% as poor (C), and <10% as very poor (D).
[0183] Table 4 Test results
[0184]
[0185]
[0186] According to Table 4, the photosensitive compositions provided by Examples 1-15 of the present invention all have high sensitivity, excellent low warpage stress, and excellent chemical resistance. Compared with the examples, Comparative Example 1 has no contrast, and the loss of developed film thickness is large, and Comparative Example 2 has poor toughness and poor sensitivity. Comparative Example 3 has high warpage stress, poor sensitivity, and poor chemical resistance.
[0187] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A photosensitive composition, characterized in that The invention comprises a component (a) a graft polymer, which is selected from the compound represented by the following formula 1: wherein Ar1 is selected from a tetravalent organic group, Ar2 is selected from a divalent organic group, R′ is selected from any one of an alkyl group, an alkoxy group, a cycloalkyl group and an aromatic group; m+n=5-200, n / (m+n)=0.05-1, k=2-10, x=0.5-10; Component (b) a photoacid generator; Component (c) thermal crosslinking agent: a crosslinking agent containing CH2OR", wherein R" is selected from hydrogen or a monovalent organic group; Component (d) a basic compound.
2. The photosensitive composition according to claim 1, characterized in that Ar1, when it appears each time, is selected from any one of the tetravalent organic groups represented by the following formulae 2-1 to 2-9, either identically or differently: Wherein, R1-R8 are all monovalent organic groups, X is a divalent group, Preferably, R1-R8 are each independently selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl; Preferably, R1-R8 are each independently selected from any one of hydrogen, fluorine atom, methyl and trifluoromethyl; Preferably, X is selected from any one of an oxygen atom, a C1-C5 substituted or unsubstituted alkylene group, a sulfur atom, a sulfone group and a carbonyl group; Preferably, X is selected from any one of an oxygen atom, a methylene group, a sulfur atom, a sulfone group, a carbonyl group, C(CH3)2 and C(CF3)2; Preferably, Ar2 is selected from any one of the divalent organic groups represented by the following formulae 3-1 to 3-12, the same or different each time it appears: Among them, R9-R 20 are all monovalent organic groups, and Y is a divalent group; Preferably, R9-R 20 Each is independently selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl; preferably, R9-R 20 Each is independently selected from any one of hydrogen, fluorine, methyl and trifluoromethyl; Preferably, Y is selected from any one of an oxygen atom, a C1-C5 substituted or unsubstituted alkylene group, a sulfur atom, a sulfone group and a carbonyl group; Preferably, Y is selected from any one of an oxygen atom, a methylene group, a sulfur atom, a sulfone group, a carbonyl group, C(CH3)2 and C(CF3)2.
3. The photosensitive composition according to claim 1, characterized in that The component (b) is a compound that generates acid when irradiated with 365 nm light; Preferably a triarylsulfonium salt; More preferably, the sulfonate anion contained in the triarylsulfonium salt is a fluorine-containing sulfate anion.
4. The photosensitive composition according to claim 1, characterized in that The component (c) is selected from the compounds represented by formula 4-2-1 and / or formula 4-2-2, In formula 4-2-1, R 21 are each independently a hydrogen atom or a monovalent organic group, R 22 Each is independently a hydrogen atom or a monovalent organic group, and may be combined with each other to form a ring structure which may have a substituent; In formula 4-2-2, R 23 is selected from a hydrogen atom or a monovalent organic group, R 24 is selected from a monovalent organic group, n is an integer of 1-4, X is selected from a single bond or a 1-4 valent organic group; a is an integer of 1-4, b is an integer of 0-3, when a is 2, 3 or 4, R 23 The same or different, when b is 2 or 3, R24 are the same or different; Preferably, component c is selected from any one of the compounds represented by the following structural formulas: Among them, R 25 is an alkyl group having 1 to 20 carbon atoms, preferably an alkyl group having 1 to 6 carbon atoms, R 26 It is an alkyl group having 1 to 10 carbon atoms.
5. The photosensitive composition according to claim 1, characterized in that Component (d) is selected from the compounds represented by the following structural formula: Wherein, A, Y and Q are independently selected from one of alkyl, alkoxy and cyclic alkyl; Preferably, the component (d) is selected from any one of the compounds represented by the following structural formulas:
6. The photosensitive composition according to any one of claims 1 to 5, characterized in that: Based on 100 parts by weight of the component (a), the content of the component (b) is 1-5 parts by weight, the content of the component (c) is 5 parts by weight or more, and the content of the component (d) is 0.001-2 parts by weight; Preferably, component (c) is 10 parts or more, more preferably 5-30 parts by weight; Preferably, the molar ratio of component (b) to component (d) is 2.5-300, preferably 7.0-150.
7. The photosensitive composition according to any one of claims 1 to 5, characterized in that: The photosensitive composition further contains any one or a combination of at least two of a silane coupling agent, a solvent and a leveling agent; Preferably, based on 100 parts by weight of the component (a), the content of the silane coupling agent is 0.5-15 parts by weight, the content of the solvent is 50-1000 parts by weight, and the content of the leveling agent is 100-1000 ppm.
8. A method for preparing a pattern, characterized in that: The method comprises coating the photosensitive composition according to any one of claims 1 to 7 on a supporting substrate; Preferably, the method further comprises: drying, exposure, development and heating treatment in sequence after coating; Preferably, the light source used in the exposure process is i-ray.
9. A solidified product, characterized in that: The cured product is formed by curing the photosensitive composition according to any one of claims 1 to 7; Preferably, the cured product includes a surface protection film or an interlayer insulating film.
10. An electronic component, characterized in that: The electronic component comprises the cured product according to claim 9.
Citation Information
Cited By
Photosensitive composition, method for preparing pattern, cured product, and electronic component
EP4772942A1
Photosensitive composition, method for preparing pattern, cured product, and electronic component
WO2026097702A1
